(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article analyses one of the most important cross-cultural communication aspects – the linguistic aspect. Within verbal communication this aspect shows cultural and social individualities of addresser, using linguistic means of communication.